2017
DOI: 10.1002/jcb.25907
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Protective Effects and Mechanisms of Diallyl Disulfide on Interlukin‐1β‐Induced Oxidative Stress and Mitochondrial Apoptotic Signaling Pathways in Cultured Chondrocytes

Abstract: The protective effects and mechanisms of DADS on IL-1β-mediated oxidative stress and mitochondrial apoptosis were investigated in C28I2 human chondrocytes. The effect of various concentrations of DADS (1, 5 10, 25, 50, and 100 μM) on C28I2 cell viability was evaluated in different times (2, 4, 8, 16, and 24 h) to obtain the non-cytotoxic concentrations of drug by MTT-assay. The protective effect of non-toxic concentrations of DADS on experimentally induced oxidative stress and apoptosis by IL-1β in C28I2 was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…Wu et al (2016) observed that S-propargyl-cysteine, an endogenous inductor of H 2 S synthesis, activates Nrf-2 signaling in adjuvant-induced arthritis rats and inhibits inflammatory response, ameliorating the severity of the arthritis model [ 46 ]. Hence, a growing number of evidences suggest that the Nrf-2 activation induced by H 2 S is also responsible for its anti-inflammatory effects [ 46 , 63 , 64 ]. In our study, we observed for the first time that the administration of a slow-releasing H 2 S donor in the joint induces the expression of Nrf-2 in the cartilage and that this event could contribute to the attenuation of the expression of pro-inflammatory markers detected in our model and subsequently to its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (2016) observed that S-propargyl-cysteine, an endogenous inductor of H 2 S synthesis, activates Nrf-2 signaling in adjuvant-induced arthritis rats and inhibits inflammatory response, ameliorating the severity of the arthritis model [ 46 ]. Hence, a growing number of evidences suggest that the Nrf-2 activation induced by H 2 S is also responsible for its anti-inflammatory effects [ 46 , 63 , 64 ]. In our study, we observed for the first time that the administration of a slow-releasing H 2 S donor in the joint induces the expression of Nrf-2 in the cartilage and that this event could contribute to the attenuation of the expression of pro-inflammatory markers detected in our model and subsequently to its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, the harmful production of endogenous ROS is balanced by the antioxidant defence system including enzymes like SOD-2, CAT and GPx, to decrease oxidative stress. SOD-2 or manganese-dependent (Mn)-SOD represents one of the three SOD family members; it is located in the mitochondrial matrix of the cells and catalyzes the dismutation of superoxide anion in O 2 and H 2 O 2 , which is then turned in water, to CAT and GPx [ 29 , 30 ]. In vivo and in vitro studies have demonstrated the reduction in expression and activity of these stress-related enzymes in OA chondrocytes, leading to the loss of their ability to scavenge ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Garlic possesses nutritional values and medicinal characteristics. Diallyl disulfide (DADS) is the main organosulfur ingredient in garlic, and has shown diverse pharmacological properties such as anti-inflammation [ 14 , 15 ], anti-oxidation [ 16 , 17 , 18 , 19 , 20 ] and immune regulation [ 21 ]. The anti-inflammatory effects of DADS observed can be attributed to its ability to decrease inflammatory mediators by inhibiting NF-κB translocation and i-κB phosphorylation, as well as suppressing the expression of mRNA for IL-1β and TNF-α [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%